Factores asociados a la automedicación durante la pandemia de COVID-19 en pobladores del distrito de Cutervo - Vilchez Altamirano, Jhon Alex (2025)
OBJECTIVE: To evaluate the factors associated with self-medication during the COVID-19 pandemic among residents of the Cutervo district. METHOD: A quantitative, observational, descriptive, and correlational study with a cross-sectional design. A total of 380 people over 18 years of age were surveyed using non-probability convenience sampling. A validated questionnaire and statistical tests using SPSS v27.0 and Microsoft Excel 2019 were used. RESULTS: Age was significantly associated (p = 0.000), as was sex (p = 0.026), with a higher prevalence in men (80.2%) than in women (69.5%). Likewise, self-medication was more common in rural areas (78.6%) than in urban areas (66.5%) (p = 0.000), associated with a lower educational level (p = 0.001) and both financial dependence on children and not being dependent on anyone (p = 0.018), favored by recommendations from friends and family (p = 0.000). It is also noteworthy that the most commonly used self-medication medications were paracetamol (71.9%), traditional medicine (42.8%), ivermectin (22.3%), anti-inflammatory drugs (19.1%), antibiotics (17.6%), and chlorine dioxide (2.9%), motivated by fear of infection (42.1%) and the attempt to prevent the disease (41.0%). CONCLUSION: Self-medication was common, influenced by demographic, economic, and cultural factors. A higher incidence among men, rural residents, and people with less education will be monitored. Misinformation and family influence promoted the use of medications without scientific evidence, reinforced by the fact that most users reported achieving the expected effects and experiencing no complications